2021
DOI: 10.3390/rs14010064
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Invasive Plant Species with Hyperspectral Data Based on Iterative Accuracy Assessment Techniques

Abstract: Recent developments in computer hardware made it possible to assess the viability of permutation-based approaches in image classification. Such approaches sample a reference dataset multiple times in order to train an arbitrary number of machine learning models while assessing their accuracy. So-called iterative accuracy assessment techniques or Monte-Carlo-based approaches can be a useful tool when it comes to assessment of algorithm/model performance but are lacking when it comes to actual image classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
4
12
0
Order By: Relevance
“…The results of the classification also depend on the vegetation period in which the airborne data were acquired. It was confirmed that the optimal image acquisition period for plant communities mapping is from the second half of August to the first half of September in Central European vegetation periods, due to the complex physiognomy [13][14][15]78]. This was also confirmed by Calvão and Palmeirim [9], who observed a summer stress (an intense radiation and a water deficit), which changed the registered spectra of different types of vegetation included in the shrubby formations.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The results of the classification also depend on the vegetation period in which the airborne data were acquired. It was confirmed that the optimal image acquisition period for plant communities mapping is from the second half of August to the first half of September in Central European vegetation periods, due to the complex physiognomy [13][14][15]78]. This was also confirmed by Calvão and Palmeirim [9], who observed a summer stress (an intense radiation and a water deficit), which changed the registered spectra of different types of vegetation included in the shrubby formations.…”
Section: Discussionsupporting
confidence: 54%
“…In our case, signature pixel values representing different classes were selected from field-verified training polygons and randomized sampled (50:50) as training/validation patterns, limiting the phenomenon of overfitting during classification [77]. Each classification iteration used 500 trees (ntree parameter), which comes from the optimization process to obtain repetitive results [78,79]. The SVM, as a non-parametric classifier, allowed for a flexibility of training data, thus limiting errors and leading to high accuracy [28,80].…”
Section: The Classification Algorithm and Accuracy Assessmentmentioning
confidence: 99%
“…During splitting, it was ensured that pixels from a single polygon were included in the training or test set to ensure their independence and non-spatial correlation [71]. An iterative accuracy assessment [72] procedure was applied, during which the classification procedure was repeated 100 times, assessing the overall accuracy (OA), the kappa coefficient [73], producer and user accuracy (PA and UA) [74], and the F1-score (F1) for all classes each time based on randomized selected verification pixels from the validation set [75,76]. It helped visualize all results using box graphs presenting the median with a 95% confidence interval and first and third quartiles (Q1, Q3), between Then, using the R language 4.0.3 [66], pixel values were extracted from the data using the raster and rgdal [67] packages.…”
Section: Sensormentioning
confidence: 99%
“…This is important for tracking the dynamics of invasion and an assessment of threats to biodiversity. Most works have used aerial data or high-resolution satellite imagery; Sabat-Tomala et al [8], based on airborne hyperspectral HySpex images, Random Forest (RF), and Support Vector Machine (SVM) algorithms, classified three species of expansive and invasive plants (including Solidago spp.) with accuracy of around 0.90 (F1-scores), emphasizing that the results obtained for spring, summer, and autumn images were similar, and the fusion of all the data allowed goldenrod to be mapped with an F1-score of 0.99.…”
Section: Introductionmentioning
confidence: 99%